Dynamic and structural insights into allosteric regulation on MKP5 a dual-specificity phosphatase - Erin Skeens; Federica Maschietto; Ramu Manjula; Shanelle Shillingford; James Murphy; Elias J. Lolis; Victor S. Batista; Anton M. Bennett; George P. Lisi (Nature Communications)
Abstract Dual-specificity mitogen-activated protein kinase (MAPK) phosphatases (MKPs) directly dephosphorylate and inactivate the MAPKs. Although the catalytic mechanism of dephosphorylation of the MAPKs by the MKPs is established, a complete molecular picture of the regulatory interplay between the MAPKs and MKPs still remains to be fully explored. Here, we sought to define the molecular mechanism of MKP5 regulation through an allosteric site within its catalytic domain. We demonstrate using crystallographic and NMR spectroscopy approaches that residue Y435 is required to maintain the structural integrity of the allosteric pocket. Along with molecular dynamics simulations, these data provide insight into how changes in the allosteric pocket propagate conformational flexibility in the surrounding loops to reorganize catalytically crucial residues in the active site. Furthermore, Y435 is required for the interaction with p38 MAPK and JNK, thereby promoting dephosphorylation. Collectively, these results demonstrate critical roles for the allosteric site in coordinating both MKP5 catalysis and MAPK binding.